POTENSI EKSTRAK ETIL ASETAT Coprinus comatus TERHADAP KADAR UREUM DAN KREATININ PADA TIKUS PUTIH MODEL DIABETES - Anik Laeli Perdanawati; Nuniek Ina Ratnaningtyas; Hernayanti Hernayanti (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Coprinus comatus or chicken drumstick mushrooms has potential as antioxidant and antidiabetic. Hyperglycemia in people with diabetes mellitus causes an increase in Reactive Oxygen Species (ROS). Pancreatic β cells have less antioxidants than other organs. This causes oxidative stress which triggers a chain reaction of lipid peroxidation which damages the kidneys and disturbs the glomerular filtration rate. Impaired glomerular filtration rate is characterized by increased levels of urea and creatinine. Flavonoids in C. comatus are able to donate H + and stop lipid peroxidation reactions in the kidneys, so that urea and creatinine levels decrease.This study aims to determine the effect of C. comatus ethyl acetate extract on blood urea and creatinine levels in diabetic rats and to determine the effective dose of C. comatus ethyl acetate extract on blood urea and creatinine levels in diabetic rats. This study used an experimental method based on a completely randomized design (CRD). The data obtained from the measurement of urea and creatinine levels were analyzed using the one way Anova statistical test at the 95% confidence level and followed by Duncan's test at an error rate of 5%. The results of this study indicated that the ethyl acetate extract of C. comatus affected the blood urea and creatinine levels of diabetic rats. C. comatus extract at a dose of 500 mg/kgBW is an effective dose that has an effect on reducing levels of blood urea and creatinine in the amount of 16,66 ± 0,00 mg/dL dan 0,40 ± 0,12 mg/dL.